(untitled) (Journal of Social Sciences Review, 2023)
Digitalization decreases job satisfaction by increasing pressure, fear of job loss, and deteriorating work-life balance. The study investigates the nexus of customer incivility, workplace incivility, employee religious perception, digitalization, HRM practices, and employee turnover intention in the presence of practical commitment as a mediator and servant leadership as a moderator. Further, the current study also examines the relationship between practical commitment and employee turnover intention. Data was collected through a self-administrator questionnaire from frontline employees of private banks in Punjab, Pakistan. Data analysis was done through SPSS and PLS software. The current study results have revealed that WPI, CI, ERP, DEG, and HRM practices are significantly associated with employees’ job attitudes, such as EC and TI. Further, Effective commitment positively mediates relationships. Moreover, servant leadership successfully moderates the relationship between EC and TI. In light of the above results, the current study recommended that WPI, CI, ERP, DEG, and HRM practices are significant factors for the future success of the service sector in developing countries like Pakistan. The current study contributes to the literature on Change, IT revolution, digitalization, and its adverse effects through the lens of resource conservation theory to explain the phenomena of turnover intention framework, which is the uniqueness of the current study.